(untitled) (Scientific journal of the Fergana State University, 2026)
The aim of this article is to obtain a new type of polymer material by recycling low-density polyethylene waste based on chemical binders and fillers, as well as to study the fire-resistant properties of the obtained new type of polymer material. To obtain a new type of polymer material, sulfur and melamine were used as chemical binders, and bitumen, natural wool and aluminum oxide were used as fillers. This material describes the formation of bonds between melamine and sulfur molecules when secondary polyethylene is added to the composition. The fire resistance of the obtained new type of polymeric materials was studied using the “Combustible Pipe” method in accordance with GOST requirements. During the study, the oxygen index of the polymer material obtained by adding various additives was compared with the oxygen index of recycled polyethylene. Based on the obtained results, it was proven that aluminum oxide and melamine, which have a high melting point and are part of secondary polyethylene, contribute to increasing the fire resistance of the polymer material.